Orgasmic Bodies - Frith, Hannah. author. aut Link
X, 192 p.
Keywords: Orgasmic Bodies explores how bodily experiences of orgasm are worked up as present/absent, complicated/straightforward, too slow/too fast, fake or real, in the doing of masculinities and femininities. Engaging with both science and popular culture it examines the meanings given to orgasmic bodies in contemporary heterosex.